Low typing endurance in keyboard workers with work-related upper limb disorder - Povlsen, Bo (Royal Society of Medicine Press, 2011)
OBJECTIVE: To compare results of typing endurance and pain before and after a standardized functional test. DESIGN: A standardized previously published typing test on a standard QWERTY keyboard. SETTING: An outpatient hospital environment. PARTICIPANTS: Sixty-one keyboard and mouse operating patients with WRULD and six normal controls. MAIN OUTCOME MEASURE: Pain severity before and after the test, typing endurance and speed were recorded. RESULTS: Thirty-two patients could not complete the test before pain reached VAS 5 and this group only typed a mean of 11 minutes. The control group and the remaining group of 29 patients completed the test. Two-tailed student T test was used for evaluation. The endurance was significantly shorter in the patient group that could not complete the test (P < 0.00001) and the pain levels were also higher in this group both before (P = 0.01) and after the test (P = 0.0003). Both patient groups had more pain in the right than the left hand, both before and after typing. CONCLUSIONS: Low typing endurance correlates statistically with more resting pain in keyboard and mouse operators with work-related upper limb disorder and statistically more pain after a standardized typing test. As the right hands had higher pain levels, typing alone may not be the cause of the pain as the left hand on a QWERTY keyboard does relative more keystrokes than the right hand.